The prevalence of Shift Work Sleep Disorder and The Quality Of Sleep Among Nurses Working in Selected Hospitals, Hyderabad - Anumol Joseph; Sister Mary Brooke; Jelby; Pushpalatha; Sharon; Sunitha (Indian Journal of Psychiatric Nursing)
Now a days the shift work is one of the most important cause for sleeping disorders among nurses. In almost every occupation round the clock performance is expected and the census data shows that there is a large segment of the work force is employed on nonstandard work schedule which may include shift work. A study was conducted with the aim to assess the occurrence of shift work disorder (SWD)and quality of sleep among staff nurses in a selected hospital of Hyderabad. Methods: The study was conducted in a private hospital of Hyderabad, Telangana. The sample size was 60 staff nurses of a selected multispecialty hospital of Hyderabad. The tools selected for the study was Pittsburgh's sleep quality index and a questionnaire was developed for assessing shift work disorder prepared by reviewing the literature, Bergen's shift work disorder and global sleep disorder scale. Result: The result of the study revealed that 83.3% had mild Shift Work Disorder followed by moderatemild SWD16.6% and surprisingly no mild SWDand severe mild SWD were reported by the staff nurses. In regards to sleep quality, majority of the nurses that is 70% reported to have poor quality of sleep whereas only 30% of the nurses reported to have good quality of sleep. There was no association found between prevalence of shift work sleep disorders and age, marital status and duration of sleep. In conclusion, reducing night work exposure appears to be the best intervention strategy for preventing SWD. A high prevalence of SWDsymptoms may call for a focus on the systemic antecedents of work related sleep problems.